Vancomycin overuse in Siriraj Hospital - Pinyo Rattanaumpawan (2018)
Objective: An emergence of vancomycin resistant organisms particularly vancomycin-resistant enterococci (VRE) has become a serious public health concern. To prevent and control the spread of vancomycin resistant organisms, the prudent use of vancomycin is strongly recommended by the Hospital Infection Control Practices Advisory Committee (HICPAC). Material and Method: A 6-week prospective observational study of vancomycin use was conducted in hospitalized patients at Siriraj Hospital from February to March 2005. Indications of initiating and continuing vancomycin were categorized according to HICPAC recommendations. Factors related to the appropriateness of vancomycin use were also evaluated. Results: At initiation, vancomycin was inappropriately and empirically prescribed 19/222 times (8.6%) and 166/222 times (74.8%), respectively. After microbiological results were obtained, the rate of inappropriate prescription continued 132/222 times (59.5%). Furthermore, inappropriate use was significantly correlated with the type of department. There was a higher rate in the Department of Pediatrics, Surgery and Ophthalmology when compared with that of the Department of Medicine (p = 0.001). The inappropriate use also correlated with topical use (p < 0.001), intravenous administration (p = 0.012) and no consultation with an infectious disease specialist (p = 0.001). The overuse did not improve the clinical outcome. Conclusion: A substantial rate of inappropriate use of vancomycin was found in Siriraj Hospital. Intervention to improve appropriateness of vancomycin use should be urgently implemented to prevent and control the emergence of vancomycin resistant organisms.